Implementation of a Digital Educational Tool in the Quechua Language for Learning Mathematics among Quechua-Speaking Children - Saldivar Contreras, Luis Alberto (2025)
This study investigated the impact of a digital educational tool developed in the Quechua language on the mathematical learning of second-grade Quechua-speaking children in Apurímac, Peru. Employing a quasi-experimental design, the research compared the performance of an Experimental Group (EG) using the Quechua-language tool with a Control Group (CG) receiving traditional instruction. The tool was designed to address linguistic, pedagogical, technological, and evaluative dimensions of learning. Pre- and post-test results revealed significant improvements in the EG across all dimensions (p < 0.05), with post-test scores in the EG (M = 32.13) substantially higher than those in the CG (M = 19.47). The study underscores the efficacy of digital tools in fostering active and contextualized learning, particularly in linguistically diverse settings. However, challenges such as insufficient teacher training and lack of culturally adapted materials persist, highlighting the need for comprehensive strategies to support bilingual education. The results advocate the integration of native language-based digital tools in educational curricula to promote equity, cultural preservation, and academic success among Indigenous populations. This research contributes to the growing body of evidence supporting Intercultural Bilingual Education as a means to address linguistic and cultural disparities in educational outcomes and can be replicated in other contexts.